1987
DOI: 10.1017/s0950268800067832
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alcohol shock enrichment and selective enrichment for the isolation ofClostridium difficile

Abstract: SUMMARYTwo enrichment methods were compared for their ability to recover Clostridium difficile from stool samples. One method used selective enrichment in an antibioticcontaining broth followed by detection with a latex particle agglutination (LPA) reagent. The other used enrichment in a non-selective broth following treatment of the specimen with alcohol. With clinical specimens enrichment culture was significantly more successful at detecting C. difficile than direct plating. Alcohol shock enrichment was twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Total C. difficile cells (vegetative cells and spores) or only spores (ethanol resistant) in fecal samples can easily be enumerated using CCEY selective medium in combination with the ethanol shock method (47). We found that immediately after excretion 10 to 20% of the total C. difficile vegetative cells and spores shed in the feces of supershedders were spores (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Total C. difficile cells (vegetative cells and spores) or only spores (ethanol resistant) in fecal samples can easily be enumerated using CCEY selective medium in combination with the ethanol shock method (47). We found that immediately after excretion 10 to 20% of the total C. difficile vegetative cells and spores shed in the feces of supershedders were spores (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Enrichment culture, in addition to culture on solid media, was used in the present study, while the earlier work relied on the use of solid media (CCFA with 0.1 % sodium taurocholate) and an alcohol shock procedure [3]. In a previous study [14] comparing enrichment culture and the alcohol shock procedure, enrichment was significantly better than alcohol shock.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is no consensus on the best method for recovery of the organism in culture. Some investigators have employed a heat shock or alcohol shock prior to inoculation to enhance spores of C. difficile and inhibit growth of other organisms (66)(67)(68). A variety of different medium formulations have been described, many of which take advantage of the fact that C. difficile can ferment fructose (69,70).…”
Section: Laboratory Methods For Clostridium Difficile Detection Methodsmentioning
confidence: 99%